Implementasi Teknologi Drone di Kelompok Tani untuk Monitoring Bukaan Lahan Pertanian Secara Cepat dan Akurat pada Lahan Cetak Sawah Rakyat di Desa Basarang, Kabupaten Kapuas: Implementation of Drone Technology in Farmer Groups for Fast and AccurateMonitoring of agricultural Land Clearing in Basarang Village, Kapuas Regency - Prayoga, Reksa; Lutfi, M Wasilul; Prabowo Rahardjo, Seto Sugianto; Agung, Prasetyo; Prasetyorini, Linda; Asmaranto, Runi (Fakultas Pertanian Universitas Brawijaya, 2025)
Rice fields are the main source of food production that requires continuous monitoring to maintain their sustainability. This community service activity aims to implement drone technology for monitoring rice field openings in the People's Rice Field Program as part of the application of precision agriculture at the farmer level. The activity was carried out through a participatory approach involving several stakeholders, namely farmers as partners, agricultural extension workers and village officials, as well as students. The community service methods included training in drone operation, field practice in aerial imaging, and spatial data processing and interpretation using a Geographic Information System (GIS). The results show that the use of drones can increase the efficiency of monitoring time, expand the coverage of the monitoring area, and produce accurate and easy-to-understand spatial information. The visualization of aerial images and land clearing maps helps farmers understand the condition of rice fields objectively and supports data-based land management. The integration of community service activities with students also provides practical learning benefits for students while strengthening the process of technology transfer to partners. Overall, the implementation of drone technology has the potential to support the application of precision agriculture and sustainable rice field management, as well as contribute to strengthening food security at the local level.